Research on brain functions related to visual information processing and body coordination function of pilots based on the low-frequency amplitude method - Xu, Kaijun; Liu, Rui; Chen, Xipeng; Chen, Xi; Yang, Yong; Wang, Quanchuan; Yang, Jiazhong (Frontiers in Human Neuroscience, 2023)
Safety is the lifeline of civil aviation. This article uses the resting-state functional magnetic resonance imaging low-frequency amplitude analysis method to evaluate pilots and ordinary ground workers in the classical frequency band (0.01~0.08Hz) and sub-frequency band (slow-5 frequency band:0.01~0.027Hz, slow-4 frequency band:0.027~0.073Hz) to detect low-frequency amplitude changes, explore the frequency-dependent changes of pilots' low-frequency amplitudes, and provide an evaluation reference for pilots’ professionalism lifecycle management planned by the Civil Aviation Administration of China.Resting-state functional magnetic resonance data were collected from 26 pilots (flight group) and 23 ordinary ground workers (control group), and the average low-frequency amplitude (mALFF) of the classical frequency band and sub-frequency band was calculated. The two-sample t-test was performed in SPM12 to compare the differences between the two groups of data in the classic frequency band. A mixed design analysis of variance was used to compare the main effects and the inter-band effects of the two sets of low-frequency amplitude data under the sub-frequency bands and to compare the differences between the low-frequency amplitude values in the slow-5 frequency band and the slow-4 frequency band. In the classic frequency band, there was a significant difference between pilots' left cuneiform lobe and the right cerebellum 6 area compared with the control group. The main effect results between the sub-frequency bands show that compared with the control group, the area with the higher mALFF value in the flight group was mainly located on the left side. In the middle occipital gyrus, the left cuneiform lobe, the right superior occipital gyrus, the right superior gyrus, and the left lateral central lobule. The area where the value of mALFF decreased was mainly located in the left rectangular cleft, its surrounding cortex and the right dorsolateral superior frontal gyrus. Compared with the slow-4 frequency band, the mALFF value of the left middle orbital middle frontal gyrus of the slow-5 frequency band was increased, while the mALFF value of the left putamen, left fusiform gyrus, and right thalamus was decreased. The sensitivity of the slow-5 frequency band and the slow-4 frequency band to the pilots' different brain areas was also different.